Kekurangan energi kronik dan tinggi badan ibu terhadap kejadian stunting pada balita - Andri Yulianto; Resi Hana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Chronic energy deficiency and maternal height on the incidence of stunting in toddlersBackground: Factors that influence stunting according to WHO in 2013 include family factors such as maternal malnutrition (before pregnancy, pregnancy and breastfeeding, breastfeeding), maternal height status, teenage pregnancy, infection, birth babies (IUGR and Premature), short babies / LBW and Hypertension.Purpose:The objective of this research was to find out the correlation of maternal nutrition status and health condition to children under five stunting in Kota public health center working area in Pesawaran district in 2019. Method: This was a research by using survey case control approach. Research subjects were 4,310 parents reported in Maternal and Child and Nutiriton Report. There were 256 children under five (8-59 months) reported with stunting to be measured with anthropometry. 172 respondents were taken by using systematic random sampling. Secondary data were collected by using observation sheets. Data were analyzed by using chi square test. Results: Bivariate analysis result showed that there were correlations of maternal nutrition status and health condition (p-value 0.013; OR=2.289) and body height (p-value 0.002; OR=2.76) to stunting case. The researcher recommends mothers with shorter heights to consume nutritional supplements to fulfill energy, protein, fat, and other macro and micro nutrition to prevent and mitigate stunting, so that genetic factors can be mitigated with good nutritional intake. Conclusion: All independent variables are associated with the incidence of stunting.Keywords: Chronic Energy Deficiency; Mother's Height; Toddler; StuntingPendahuluan: Faktor yang mempengaruhi stunting menurut WHO tahun 2013 salah satunya faktor keluarga yaitu faktor ibu kekurangan nutrisi (saat sebelum hamil, hamil dan menyusui, masa menyusui), status tinggi badan ibu, kehamilan remaja, infeksi, bayi lahir (IUGR dan Premature), bayi pendek/BBLR dan Hipertensi. (Lamid, 2015).Tujuan: Untuk mengetahui hubungan KEK dan tinggi badan ibu terhadap kejadian stunting pada balita di wilayah kerja UPT Puskesmas Kota Dalam Kabupaten Pesawaran tahun 2019.Metode:Desain penelitian menggunakan survey case control.. Subjek penelitian ini adalah orang tua yang memiliki balita yang tercatat dilaporan Gizi dan KIA dengan populasi sebanyak terdapat 4.310 bayi balita usia 8 – 59 bulan yang diukur antropometri dengan angka stunting sebanyak 256 bayi balita usia 8 – 59 bulan dan sampel sebanyak didapatkan 172 bayi balita dengan teknik sampling systematic random sampling. Jenis data menggunakan data sekunder dengan menggunakan lembar observasi. Analisa data menggunakanchy square.Hasil: Di dapatkan uji statistik bivariat didapatkan ρ – value KEK = 0,013 dan OR = 2,289 dan ρ – value tinggi badan = 0, 002 dan OR = 2,76.Simpulan: Seluruh variabel independen berhubungan dengan kejadian stunting.